Characterization and field emission properties of ZnMgO nanowires fabricated by thermal evaporation process - Yousefi, R.; Sheini, F.J.; Muhamad, M.R.; More, M.A. (Elsevier, 2010)
In this paper, we in vestigate the roles of gold catalyst using modified thermal evaporation set-up in the growth process of ZnMgO nanowires. ZnMgO nanowires are fabricated on silicon substrates using different thickness of gold catalyst. A simple horizontal double-tube system along with chemical vapor diffusion of the precursors, based on Fick's first law, is used to grow the ZnMgO nanowires. Field emission scanning electron microscopy images show that the ZnMgO nanowires are tapered. The optical properties of the ZnMgO nanowires are characterized by room temperature photoluminescence (PL) measurements. The PL studies demonstrate that the ZnMgO nanowires grown using this method have good crystallinity with excellent optical properties and have a larger band-gap in comparison to the pure ZnO nanowires. Field emission characterization shows that the turn-on field for the nanowires grown on the thinner gold film is lower than those grown on the thicker gold film. (C) 2010 Elsevier Masson SAS. All rights reserved.